Acute Flaccid Myelitis Cases Presenting During a Spike in Respiratory Enterovirus D68 Circulation: Case Series From a Single Pediatric Referral Center. (4th October 2017) - Naccache, Samia; Bender, Jeffery; Desai, Jay; Van, Tam; Meyers, Lindsay; Jones, Jay; Mongkolrattanothai, Kanokporn; Bard, Jennifer Dien
Abstract: Background: In 2014, a global outbreak of Enterovirus D68 (EV-D68) caused severe respiratory disease and was associated with an increase in acute flaccid myelitis (AFM) cases. Despite heightened surveillance, both EV-D68 detection and AFM reporting dropped in 2015. As AFM reporting increased in 2016, we sought to better understand AFM and EV-D68 epidemiology at our institution. Methods: Chart review of clinical presentation and workup was conducted on patients meeting the case definition for AFM for 2015-16. To determine EV-D68 prevalence at CHLA, samples positive for Rhinovirus/Enterovirus (RV/EV) by FilmArray ® Respiratory Panel (FA-RP) in September 2016 were screened for EV-D68 by RT-PCR. Results were compared with a research algorithm developed within the FilmArray ® Trend epidemiology software. After establishing accurate EV-D68 prediction, the algorithm was used on historic FA-RP assays to measure EV-D68 prevalence at CHLA in 2015 and 2016. Results: 7 patients with a median age of 3.3 years and no significant past medical history presented with AFM between July 15 - October 15, 2016, while none were identified in 2015. All had acute onset patchy weakness involving mostly the upper limbs and grey matter involvement on MRI. 6/7 reported fever/upper respiratory infection prior to AFM onset. CSF from 7/7 was negative by FilmArray ® meningitis/encephalitis Panel and 2/7 were positive for EBV DNA. Further work up on CSF and blood were negative. 4/7 (57.1%) patients were RV/EV positive from respiratory samples and 3 were confirmed as EV-D68 by RT-PCR. IVIG was given in 7/7 cases. Patients were discharged after an average of 8.8 (4.8-13.6) days. The FilmArray Trend monitoring revealed that during the time of AFM presentation in 2016, 226/778 patients tested for respiratory viruses by the FA-RP were positive for RV/EV. Of those, 29.2% (66/226) were positive for EV-D68 compared with 0.02% (2/224) over the same period in 2015. Conclusion: As shown by CDC surveillance data, we saw a resurgence of AFM cases in 2016 compared with 2015. All 7 patients identified were previously healthy and had persistent weakness at discharge. Cases were accompanied by increases in circulating respiratory EV-D68. Further investigation of the correlation between EV-D68 resurgence and AFM is warranted. Disclosures: L. Meyers, BioFire Diagnostics: Employee, Salary. J. Jones, Biofire Diagnostics LLC: Employee, Salary. J. Dien Bard, BioFire: Consultant and Investigator, Research grant and Speaker honorarium.